CNT encapsulated MnOx for an enhanced flow-through electro-Fenton process: the involvement of Mn(iv). Issue 30 (20th July 2022) - Guo, Dongli; Jiang, Shengtao; Jin, Limin; Huang, Kui; Lu, Ping; Liu, Yanbiao
Abstract : A functional electroactive CNT filter with nanoconfined MnO x nanoparticles (MnO x -in-CNT) was applied in an electro-Fenton system toward micropollutant degradation, and it exhibited superior activity and stability with limited Mn leaching. Abstract : This study reports a nanoconfined flow-through electro-Fenton system for highly efficient degradation of aqueous micropollutants. The key to such a system is a functional electroactive carbon nanotube (CNT) cathodic filter with encapsulated MnO x nanoparticles (MnO x -in-CNT). The nanohybrid filter, assisted by an electric field, generated hydrogen peroxide (H2 O2 ) in situ, followed by its subsequent conversion to reactive oxygen species (ROS) accompanied by the redox cycling of Mn(iv )/Mn(iii ). Compared with the filter consisting of MnO x coated on the surface of CNT (MnO x -out-CNT), the MnO x -in-CNT filter demonstrated a 2.9 times higher k L value (0.050 min −1 vs. 0.017 min −1 ) toward the degradation of bisphenol A (BPA). Density functional theory (DFT) computation and experimental studies revealed that the dominant ROS in the confined MnO x -in-CNT system were high-valent metal-oxo species (Mn(iv )) rather than the traditional hydroxyl or superoxide radicals in the unconfined MnO x -out-CNT system. The flow-through configuration outperformed a conventional batch reactor in BPA degradation due to convection-enhanced mass transport. These findings may provide a novel strategy for environmental remediation using highly efficient and integrated systems based on materials science, Fenton chemistry, and microfiltration techniques.